Analisis pengaruh kesadaran wajib pajak, sanksi pajak, dan program pemutihan pajak terhadap kepatuhan pembayaran pajak kendaraan bermotor di Kota Malang: Introduction - Velisya Thensy; Pujo Gunarso (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2026)
This study aims to analyze the effect of taxpayer awareness, tax sanctions, and tax amnesty programs on motor vehicle tax payment compliance in Malang City. The study employs a quantitative approach using primary data collected through questionnaires from 100 respondents. Data were analyzed using multiple linear regression. The results indicate that taxpayer awareness and tax sanctions have a positive and significant effect on compliance, while the tax amnesty program has no significant effect on motor vehicle tax payment compliance.